If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + x + -6 = 0 Reorder the terms: -6 + 12x + x = 0 Combine like terms: 12x + x = 13x -6 + 13x = 0 Solving -6 + 13x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 13x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 13x = 0 + 6 13x = 0 + 6 Combine like terms: 0 + 6 = 6 13x = 6 Divide each side by '13'. x = 0.4615384615 Simplifying x = 0.4615384615
| -0.33(0)-y=3 | | x^2-x-2=-4x-4 | | 12x+x=6 | | 48x^2+10x-25=0 | | 15(3+x)=75 | | 4(-x-2)-1(2-5x)=1 | | 8+4k=-10+x | | x^2+5x-5=9 | | 12x+9=141 | | x^2-13x+1=0 | | 4(-x-2)-1(-5x+2)=1 | | y=x^2-3x-9 | | x^2-4x-48=0 | | 7.5(3x+9)(8x+7)=0 | | 1.5t-1=1.7t-5 | | 7.5(3x+9)(8x+7)= | | 4(-x-2)-1(1-5x)=1 | | 2d+6-3d=-4 | | 2(5y-7)=3(y+4) | | 4x^2+24x+64=0 | | 16x=400 | | 0=3.5x-6 | | (2x+6)+(2x+1)=4(x-1)+9 | | y=0-6 | | x(0.8y)+1.3x(0.2y)=40150 | | 0.8747x+231.06=0 | | 6(x+3)-3x=3(x+1)+15 | | .24n+0.1n=9.8 | | 40x-40=0 | | -4k+2(5k+-6)=-3k-39 | | 3y-3+y+37=6y+40-4y | | x^2-19x-15=-9x-4 |